Latent Variables in Multidisciplinary Team Collaboration - Olatunji, Oluwole; Akanmu, A. (American Society of Civil Engineers (ASCE), 2014)
© 2014 American Society of Civil Engineers. Collaboration within multidisciplinary teams makes or mars project success. Empirical research findings have reinforced the need for project team partners to collaborate, particularly on BIM projects. Without collaboration, it is impossible to foster project deliverables. This study explores the descriptors of collaboration through five frameworks: governance, administration, autonomy, mutuality and, trust norms and reciprocity. The descriptors of these variables are discussed, with lesson drawn on how to reinforce collaboration in multidisciplinary project environments.